Intraindividual variability differentiated older adults with physical frailty and the role of education in the maintenance of cognitive intraindividual variability - Jingyi Wu; Jinyu Chen; Juncen Wu; Chun Liang Hsu (PLoS ONE, 2025)
Objectives Physical frailty is associated with increased risk of cognitive impairment. However, its impact on sustained cognitive processing as evaluated by intraindividual variability (IIV), and factors beneficial to IIV in physically frail older adults remain unexplored. This study aimed to quantify differences in IIV between older adults with and without physical frailty, and examine whether education facilitated maintenance of IIV. Methods This cross-sectional study included 121 community-dwelling older adults 65-90 years with/without physical frailty (PF and non-PF; n = 41 and n = 80 respectively). Physical frailty was determined via Short Physical Performance Battery. Dispersion across the seven components of the Montreal Cognitive Assessment (MoCA) was computed to ascertain IIV. Multivariate analysis of covariance was used to determine group differences in total score and IIV. Four moderation models were constructed to test the effects of education on age-total score and age-IIV relationships in PF and non-PF. Results Compared with non-PF, PF showed greater IIV ( p = .022; partial η² =  0.044). Among PF, education moderated age-total score (R-sq =  0.084, F =  5.840, p <  0.021) and age-IIV (R-sq =  0.101, F =  7.454, p =  0.010) relationships. IIV increased with age for those with five years (β =  0.313, p =  0.006) or no formal education (β =  0.610, p =  0.001). Greater than seven years of education (β =  0.217, p =  0.050) may be required to maintain IIV at older age. Conclusion IIV may be a sensitive method to differentiate physically frail older adults. Additionally, perceived cognitive benefits of education may be dependent on physical functioning.